The Use of Metaphor in Designing Dance Academy - Devin Defriza Harisdani; Idris Rivaldi (International Journal of Architecture and Urbanism, 2019)
In the context that a formal education in dance art is needed in Medan, Indonesia, therefore research about establishing dance academy needs to be done. Focusing on the problem that lies in the pride of the dancers, Metaphor appears as a solution in creating a Dance Academy in which the dancers can take pride of. By collecting data directly from the site or literature review, the appropriate way of using the metaphor is determined and interpreted into the building, thus creating an Architecture model that has a very strong bond with the dance art as a whole.